Online Dispute Resolution as an Alternative Model for Dispute Settlement in The Financial Technology Sector - Dona Budi Kharisma; Nadzya Tanazal E.Ar (Universitas Negeri Semarang, 2022)
Financial technology (fintech) is the use of technology in financial services in the digital economy era. Digital payments, peer-to-peer lending, and crowdfunding are examples of fintech that is growing rapidly in Indonesia. However, the high number of disputes in the fintech sector is an indication of the need for a dispute resolution mechanism that is fast, simple, and low-cost. In this regard, online dispute resolution (ODR) is present as an alternative dispute resolution model. ODR has many challenges, such as the existence of a legal vacuum (rechtsvacuum) regarding the ODR mechanism, internet disruption, and the weak protection of personal data in Indonesia.